2018
DOI: 10.2174/1389201019666180605125803
|View full text |Cite
|
Sign up to set email alerts
|

C(-260)T Polymorphism in CD14 Receptor Gene of Egyptians with Acute Myocardial Infarction

Abstract: CD14 C-(260)T polymorphism is not associated with incidence of acute myocardial infarction in Egyptians who showed elevated serum CD14 levels in comparison to healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Inflammation is one of the most important risk factors in the pathogenesis of ACS. Variations in multiple genes involved in inflammation, and previous studies showed that there were close relationships between PPARα, interleukin 18 (IL-18), IL-1β, SIRT2, and CD14 receptor and incidence of acute myocardial infarction [24][25][26][27] . In the present study, we found the polymorphism (rs755622) of MIF gene was significantly associated with the risk of ACS in Chinese Han population.…”
Section: Discussionmentioning
confidence: 98%
“…Inflammation is one of the most important risk factors in the pathogenesis of ACS. Variations in multiple genes involved in inflammation, and previous studies showed that there were close relationships between PPARα, interleukin 18 (IL-18), IL-1β, SIRT2, and CD14 receptor and incidence of acute myocardial infarction [24][25][26][27] . In the present study, we found the polymorphism (rs755622) of MIF gene was significantly associated with the risk of ACS in Chinese Han population.…”
Section: Discussionmentioning
confidence: 98%
“…After the assessment of eligibility using the full‐text, 19 articles were excluded. Following this procedure, we finally identified 14 relevant case–control studies (Haberbosch et al, ; Hashad et al, ; Hohda et al, ; Hubacek et al, ; Koch et al, ; Liu, Liu, & Wei, ; Longobardo et al, ; Lorenzova et al, ; Morange et al, ; Nauck et al, ; Sediri et al, ; Shimada et al, ; Unkelbach et al, ; Zee, Lindpaintner, Struk, Hennekens, & Ridker, ) containing 18 data sets. The study performed by Koch et al () contains two sub‐studies which involved MI and AMI.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 data sets included, 14 were recorded among Caucasians, three among Asians, and only one among Africans. In only one study were the controls recruited from the common population (Hubacek et al, ) and in one study the genotype frequency distributions in the control groups deviated from the HWE (Hashad et al, ). It is well established that deviations in HWE deviations, especially for a control group, are a strong indicator of technical errors during genotyping (Hosking et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation